COVID-19, lifestyle behaviors and mental health: A mixed methods study of women 6 months following a hypertensive pregnancy - Gow, Megan L.; Rossiter, Chris; Roberts, Lynne; Henderson, Maddison J.; Yang, Lin; Roche, Judith; Hayes, Erin; Canty, Alison; Denney-Wilson, Elizabeth; Henry, Amanda (Frontiers in Public Health, 2022)
Introduction: The COVID-19 pandemic introduced unprecedented challenges to both the physical and psychological health of postpartum women. The aim of this study was to determine how the COVID-19 pandemic affected the diet, physical activity and mental health of women 6 months following a hypertensive disorder of pregnancy. Methods: Mixed methods sub-study of the Blood Pressure Postpartum trial, which recruited women following a hypertensive disorder of pregnancy from six Sydney metropolitan hospitals. Cross sectional analysis of baseline quantitative data, collected at 6-months postpartum from March 2019-February 2022, and qualitative data analysis from semi-structured telephone interviews, was performed. Dates of COVID-19 lockdowns for Sydney, Australia were collected from government websites. Diet (vegetable, fruit, alcohol, take away intake) and physical activity (walking, vigorous activity, strength training frequency and duration) were assessed using the self-report NSW Population Health Survey. Depression and anxiety were assessed using the Edinburgh Depression Scale and GAD-7 scale, respectively. Outcome data were compared between women who completed surveys ‘In Lockdown’ versus ‘Not in Lockdown’ as well as ‘Prior to any Lockdown’ versus ‘During or Following any Lockdown’. Results: Of 506 participants, 84 women completed the study surveys ‘In Lockdown’, and 149 completed the surveys ‘Prior to any Lockdown’. Thirty-four participants were interviewed. There were no statistically significant differences in diet, physical activity, depression and anxiety among women who completed the survey ‘In Lockdown’ versus ‘Not in Lockdown’. ‘Prior to any Lockdown’, participants were more likely to do any walking (95% versus 89%, p=0.017), any vigorous activity (43% versus 30%, p=0.006) or any strength training (44% versus 33%, p=0.024), spent more time doing vigorous activity (p=0.003) and strength training (p=0.047) and were more likely to drink alcohol at least monthly (54% versus 38%, p<0.001) compared with ‘During or Following any Lockdown’. Conclusions: Our findings suggest that the confinements of lockdown did not markedly influence the mental health, diet and physical activity behaviours of women 6 months following hypertensive pregnancy. However, physical activity levels were reduced following the emergence of COVID-19, suggesting targeted efforts may be necessary to re-engage postpartum women with exercise. Trial registration: ACTRN12618002004246 (https://anzctr.org.au/Trial/Registration/TrialReview.aspx?id=376286&isReview=true)